Evaluation Of Safety And Efficacy Of Tab Hf-P1 In The Patients Of Haemorrhoids – An Observational Study - Dr. Veena Deo,; Kunal Kamthe,; Omkar Kulkarni,; Bharatbhushan Shrikhande,; Gayatri Ganu, (International Journal of Pharma and Bio Sciences, 2020)
Haemorrhoids are bolsters of submucosal vascular tissue found in the anal canal initial distal to the dentate line. Occurrence of which is challenging as several people with this illness will certainly not access to a medical practitioner. The exact cause of symptomatic haemorrhoids is unknown; many factors are believed to play a role. Management of these piles is not an easy task as most of the patients seek clinical assistance at a later stage, complicating the disease condition. Grades I through III could be effectively managed by medicinal treatment in compliant and non-complicated patients but there appear scarcity of clinically proven formulations for this indication. This appeals for the necessity to explore effective management modalities. Since classic times, herbal medicines have ascertained to be effective in the management of haemorrhoids. Tab HF-P1 is such a polyherbal formulation indicated to reverse the etiopathology of haemorrhoids by correcting the metabolism, improving liver impairment and alleviating vascular engorgement. The present study was hence proposed to evaluate the effect and safety of Tab HF-P1 in patients with haemorrhoids.